2013
DOI: 10.7314/apjcp.2013.14.12.7251
|View full text |Cite
|
Sign up to set email alerts
|

Attributable Causes of Liver Cancer Mortality and Incidence in China

Abstract: Objectives: To estimate the proportion of liver cancer cases and deaths due to infection with hepatitis B virus (HBV), hepatitis C virus (HCV), aflatoxin exposure, alcohol drinking and smoking in China in 2005. Study design: Systemic assessment of the burden of five modifiable risk factors on the occurrence of liver cancer in China using the population attributable fraction. Methods: We estimated the population attributable fraction of liver cancer caused by five modifiable risk factors using the prevalence da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
75
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(79 citation statements)
references
References 33 publications
3
75
1
Order By: Relevance
“…Hepatocellular carcinoma (HCC) is one of the most common and lethal cancer in the world (Jemal et al, 2011), and the second leading cause of cancer-related death in China, accounting for approximately half of all HCC deaths worldwide (Chen et al, 2013;Fan et al, 2013). What's worse, the overall incidence of HCC has been steadily increasing and the prognosis remains poor.…”
Section: Introductionmentioning
confidence: 99%
“…Hepatocellular carcinoma (HCC) is one of the most common and lethal cancer in the world (Jemal et al, 2011), and the second leading cause of cancer-related death in China, accounting for approximately half of all HCC deaths worldwide (Chen et al, 2013;Fan et al, 2013). What's worse, the overall incidence of HCC has been steadily increasing and the prognosis remains poor.…”
Section: Introductionmentioning
confidence: 99%
“…The population attributable fraction (PAF%) studied in 2005 in China showed that HCV was responsible for 27.7% of liver cancer deaths, while aflatoxin was estimated to be 25.0%. Alcohol drinking was responsible for 15.7% with smoking responsible for 13.9% (Fan et al, 2013). The differentially expressed genes study between cirrhosis and HCC samples showed the upregulating of ECM-receptor interaction, focal adhesion, cell adhesion molecules and other cancer-related pathways, and downregulating of complement and coagulation cascades pathways involved in HCV-induced hepatocarcinogenesis (Cheng, et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Cardiovascular disease and cancer are the main causes of death in China (Deng et al, 2014;Fan et al, 2014). Although development in prevention and treatment, these two diseases are still a great burden to patients.…”
Section: Discussionmentioning
confidence: 99%